Evaluation of Traditional and Innovative Budget Approaches in Improving Resource Allocation Efficiency - Sunaryo, Dwi; Yanti, Nofarina Maulida; Amrulloh, Rifqi; Lestari, Tina (Advances in Applied Accounting Research, 2025)
Purpose: This study evaluates the strengths and limitations of traditional and innovative budgeting approaches and their impact on resource allocation efficiency in public and private organizations. The research seeks to identify how hybrid budgeting systems can address the challenges of traditional methods while enhancing flexibility, accountability, and responsiveness in financial management. Research Design and Methodology: A qualitative systematic literature review (SLR) was conducted to synthesize insights from relevant studies on traditional and innovative budgeting frameworks, including Performance-Based Budgeting (PBB) and Zero-Based Budgeting (ZBB). The research draws from peer-reviewed academic articles, case studies, and financial management reports to comprehensively understand budgeting practices across various organizational contexts. Findings and Discussion: The findings reveal that traditional budgeting provides stability and control but lacks adaptability in dynamic environments due to its reliance on historical data and fixed expenditure categories. In contrast, innovative approaches such as PBB and ZBB enhance resource allocation efficiency by linking budgets to performance outcomes and encouraging critical evaluation of expenditures. However, these methods face challenges related to technological infrastructure, managerial readiness, and internal resistance. The discussion highlights the potential of hybrid systems that combine traditional approaches' stability with innovative methods' flexibility to create more adaptive financial management systems. Implications: This study offers valuable insights for policymakers and practitioners by recommending adopting hybrid budgeting approaches supported by cloud-based financial systems and comprehensive training programs. By fostering a culture of accountability and transparency, organizations can enhance resource allocation, improve financial performance, and build resilience to economic and policy changes.